the book of three - Alexander, Lloyd; Lloyd Alexander
Taran dreams of adventure, but nothing exciting ever happens to an assistant Pig-keeper until his pig runs away. A chase through the woods leads Taran far from home and into great danger, for evil prowls the land of Prydain. With a collection of strange and wonderful friends whom he meets on his journey, Taran finds himself fighting so that good may triumph over evil and so that his beloved home will not fall to a diabolical fiend.
Keywords: Adventure